Pengaruh Penerapan Video Pembelajaran terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Partasiwi, Nurashri; Kirana, Arinta Rara (STKIP PGRI Bandar Lampung, 2022)
The problems studied in this study are related to the low mathematical problem solving ability of students. The purpose of this study was to determine the effect of the use of learning videos on the mathematical problem solving abilities of eighth graders in odd semesters at SMP Negeri 14 Bandar Lampung in the academic year 2022/2023. This study used an experimental method with the population in this study, namely all students of class VIII Odd Semester SMP Negeri 14 Bandar Lampung, while the sample was taken two classes, namely class VIII B as an experimental class that used video learning, and class VIII C as a control class that did not use learning videos. learning video. Samples were taken using the Cluster Random Sampling technique. To determine the students' mathematical problem solving ability, the author conducted a test in the form of an essay as many as five questions which had been tested for validity and reliability. Hypothesis testing in this study uses the t-hit formula. From the results of hypothesis testing using the t-hit statistical formula, the value of t = 3,07 is obtained. From the t distribution table at a significant level of 5%, it is known that t = 1,67 then which means that the average mathematical problem solving ability of students who use learning videos is higher than the average mathematical problem solving ability of students who do not use learning videos.